Elementary Particle Masses: Alternative Model to the BEH Mechanism - Fèvre, Raymond (European Journal of Applied Sciences, 2023)
In a first paper [1], we developed a model to calculate the masses of charged leptons by quantifying the electrostatic field generated by these particles. In a second article [2], we extended this model to weak and strong interactions in order to calculate the masses of all elementary fermions. The present paper is a modified version of the second article, adding a hypothesis on the mass of dark matter particles. In this way, the model could be an alternative to the BEH mechanism of the standard model.